Three-Dimensional Video Microscopy: Potential for Improved Ergonomics without Increased Operative Time? - Samaha, Yasmina; Ray, Edward (Archives of plastic surgery, 2023)
Abstract Three-dimensional (3D) video exoscopes are high-magnification stereo cameras that project onto monitors mounted in the operating room, viewable from different angles. Outside of plastic surgery, exoscopes have been shown to successfully improve the ergonomics of microsurgery, though sometimes with prolonged operating times. We compare a single surgeon's early experience performing free flap procedures from 2020 to 2021 using either a binocular microscope or a 3D video exoscope. Ten procedures were performed with the standard operating microscope and 8 procedures with the 3D exoscope. The microsurgeon, having minimal prior experience using an exoscope, reported less neck discomfort following the free flap procedures performed with the exoscope compared with the binocular surgical microscope. Total average operating time was comparable between the standard surgical microscope and the 3D exoscope (13.7 vs. 13.4 hours, p = 0.34). Our early experience using a 3D exoscope in place of a standard optical microscope demonstrated that the exoscope shows promise, offering an ergonomic alternative during microvascular reconstruction without increasing overall operating times. Future studies will compare free flap ischemia time between cases performed using the exoscope and the conventional binocular microscope. Medical Subject Headings authorized following words: free tissue flaps; operating rooms; ergonomics; microsurgery.